Following Roman waterways from a computer screen: GIS-based approaches to the analysis of Barcino’s aqueducts - Orengo, Hèctor A.; Miró, Carme (Archaeopress, 2011)
From the 1950's until today the Roman colony of Barcino (modern Barcelona) has been believed to posses two aqueducts. One was transporting water from the Montcada mountains and the other one from the Collserola range. In this article, GIS-based least-cost route analysis (LCR) in combination with more traditional archaeological techniques is applied to analyse these aqueduct’s routes. The results obtained suggest Barcino had only one aqueduct: the one carrying water from Montcada. The aqueduct was divided in two channels before entering the city, thus giving origin to the theories suggesting the existence of two aqueducts. LCR analysis has also been useful in determining the medieval transformation of this aqueduct into the Rec Comtal water channel.